Green Behavior And The Use Of Eco-Product: Millennial Generation Perspective - Franciskus Antonius Alijoyo; Imam Sapuan (Green Publisher Indonesia, 2022)
Global warming is a problem that has not been overcome until now and even tends to get worse. This study was conducted to identify the awareness of the millennial generation as the next generation towards green behavior and the use of eco-products. This study was conducted by following a systematic literature review approach. Research data is collected from scientific journal articles indexed by Scopus and Sinta regarding green behavior and eco-products published in 2016-2021. The data is also focused on studies that make the millennial generation the subject of research. The data collected was then analyzed descriptively qualitatively. This study found that the millennial generation understands and is concerned for the environment and has begun to implement green behavior. This understanding arises because of the availability of various information both in the printed and electronic form regarding the negative impacts of global warming and climate change. Millennials' concern for the environment is shaped by their understanding and regulations to implement green behavior to create a green environment. However, based on data from various sources, the results achieved so far have not shown significant changes to overcome the problems of global warming and climate change which tend to worsen.